Epidemiological profi le of patients who dropped out of treatment for tuberculosis in a priority municipal district of Rio Grande do Sul - Lia Gonçalves Possuelo; Charlene dos Santos Silveira; Paola Teixeira dos Passos; Tamíris Cristina Hagemann Soder; Marcelo Carneiro; Luciana Fanfa; Cristiane Pimentel Hernandes Machado (Universidade de Santa Cruz do Sul, 2012)
Background and Objectives: Tuberculosis (TB) is a disease of which treatment is complex and time-consuming, resulting in high dropout rates. Abandonment leads to continuous transmission rates, increased morbidity and mortality and microbial resistance. Santa Cruz do Sul is considered one of the 15 priority municipalities in Rio Grande do Sul for tuberculosis control due to high dropout rates, low cure rates and high number of cases. Thus, the objective of this study was to describe the epidemiological profi le of patients who abandoned treatment for tuberculosis in the city of Santa Cruz do Sul, from January 2000 to December 2010. Methods: We performed a retrospective descriptive study. Data were collected from medical records of patients in the TB outpatient clinic and the System for Notifi able Diseases (Sinan). Data were tabulated and analyzed using SPSS 18.0. Descriptive statistical analyses were performed. Results: The treatment dropout rate observed in this study was 11.1%. The average age of patients who abandoned treatment was 37.2 years, 80.4% were men, 27.5% were alcoholics and 14.3% had AIDS. Conclusion: There was a high percentage of treatment dropout in the city. The dropout was significantly higher between man. Other variables associated to the dropout where not identified in this population probably due to lack of information described in the study sources. However, the improvement in the data records in the future will allow knowledge of the real epidemiological profile of these patients. Furthermore, the inclusion of a directly observed treatment and training of community health workers are essential actions to be implemented in the municipality in order to reduce dropout rates. KEYWORDS tuberculosis. treatment refusal. epidemiology.